Successful Bridge‐to‐Transplant of Functionally Univentricular Patients With a Modified Continuous‐Flow Ventricular Assist Device. Issue 1 (January 2017) - Mongé, Michael C.; Kulat, Bradley T.; Eltayeb, Osama; Zingle, Neale R.; Moss, Steven T.; Gossett, Jeffrey G.; Pahl, Elfriede; Costello, John M.; Backer, Carl L.
Abstract: A continuous flow extracorporeal ventricular assist device (VAD) was modified to support functionally univentricular infants and children awaiting heart transplantation. A centrifugal VAD, designed to flow from 1.5 to 8 L/min, was used as a bridge‐to‐transplant in four patients with functionally univentricular circulation. A variable restrictive recirculation shunt permitted lower flow ranges in small patients. In hypoxic patients, an oxygenator was incorporated into the circuit. From 2012 to 2015, the modified VAD was placed in four patients with Glenn physiology. Age ranged from 0.97 to 6.98 years (median = 2.2 yrs). Body surface area ranged from 0.41 to 0.84 m 2 (median = 0.54 m 2 ). One patient was on extracorporeal membrane oxygenation prior to VAD. A recirculation shunt was used in three patients. Three patients required temporary use of an oxygenator for 4, 10, and 27 days. Median time on the VAD was 32.3 days (range = 23–43 days). A decrease in the cavopulmonary pressure was noted in all patients, as was a fall in the B‐type natriuretic peptide. Three patients survived transplant and were discharged at 28–82 days post‐transplantation. One patient died after 35 days of support. Two patients experienced major bleeding events. Two patients experienced cerebrovascular accidents, one major and one minor. The centrifugal VAD successfully supported palliated functionally univentricular patients awaiting heart transplantation. The modified recirculation shunt facilitated the successful support of patients in whom optimal flows were substantially lower than that recommended by the manufacturer. The continuous‐flow VAD effectively decompressed the cavopulmonary system. The design allowed placement of an in‐line oxygenator in hypoxic patients. Further investigation is required to decrease the thromboembolic events, and associated morbidity, in patients supported with this device.